Sistematic Literature Review (SLR) Symbolic-Experiental Family Therapy (SEFT) - M. Bachtiar Safrudin; Hesty Eka Ardianty; Fauziyah Ardelia; Widya Aprilia; Yasinta Eka Nur Utami; Tyana Dwi Chandra; Adilah Hanani; Misliyana Moura (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Symbolic-Experiential Family Therapy (SEFT) is a family therapy approach that emphasizes emotional experience, creativity, spontaneity, and the use of symbolic processes as the foundation for change within the family system. This approach views family conflict and dysfunction as consequences of barriers in emotional expression and ineffective communication patterns, directing the therapeutic process toward reopening authentic expression and strengthening emotional connections among family members. This study aims to examine various family therapy interventions and holistic psychological approaches that effectively improve adolescent mental health, particularly for those experiencing emotional trauma and unstable family relationships. Data collection in this literature review was conducted through several databases, namely PubMed, ScienceDirect, and Google Scholar. After a selection process based on predetermined inclusion criteria, 10 articles were identified as suitable for analysis, eight of which were from Google Scholar. All selected articles were then systematically analyzed to obtain relevant findings. The results indicate that therapeutic approaches such as Symbolic-Experiential Family TherapY have been shown to reduce anxiety, improve communication, decrease family conflict, and restore emotional closeness. Additional findings show that active family involvement, including through telehealth services, enhances treatment adherence, motivation, and long-term recovery success. In conclusion, holistic family-based interventions that integrate emotional, symbolic, spiritual, creative, and structural components are more effective in helping adolescents recover from trauma and achieve emotional stability. The family plays a crucial role as the primary support system, making their involvement in the therapeutic process a key factor for successful outcomes.